ASPEK HUKUM PAJAK TENTANG PEMBERIAN INSENTIF PAJAK UNTUK WAJIB PAJAK YANG TERDAMPAK PANDEMI COVID - 19 SESUAI DENGAN PERATURAN MENTERI KEUANGAN NOMOR 9/PMK.03/2021 - ALUSIANTO HAMONANGAN; NANCI YOSEPIN SIMBOLON; RITA . (LP2MTBM MAKARIOZ, 2022)
Tax incentives are generally a fiscal stimulus given to taxpayers who are experiencing difficulties with the aim of easing thetax burden on taxpayers. The tax incentives given this time are due to the Corona Virus Disease 2019 pandemic which isendemic throughout the world and also Indonesia. To deal with the pandemic that eroded the economy, the governmentissued many policies. One of the policies issued is tax incentives for taxpayers affected by the 2019 Corona Virus Diseasepandemic as stated in the Minister of Finance Regulation Number 9/PMK.03/2021. The problems that will be examined inthis thesis include, among others, to find out what are the policy factors provided by the government for providing taxincentives to taxpayers who are affected by the Covid-19 pandemic, how to regulate and implement policies for providingBusiness Entity Tax Incentives based on Minister of Finance Regulation No. . 9/PMK/03/2021. The type of research used inthis thesis is normative and empirical legal research. The research technique obtained in this thesis is by conducting libraryresearch. A research conducted by collecting data related to the research topic in the form of primary legal materials,secondary legal materials, and tertiary legal entities. It can be concluded that this COVID-19 tax incentive can be a stimulusto the national economy. Due to the COVID-19 that is endemic in Indonesia, it has disrupted the economic conditions oftaxpayers. The tax incentives provided can reduce the suffering of taxpayers who are directly or indirectly affected by theCOVID-19 pandemic.